Using artificial intelligence in the preservation of ecosystems and biodiversity: A systematic review - Infante Villalobos, Fernando Marcelo (2026)
The use of artificial intelligence (AI) in the preservation of ecosystems and biodiversity, highlighting its applications in species monitoring, prediction of ecosystem changes, detection of illegal activities and environmental education. Benefits such as rapid data analysis, efficient ecosystem restoration and global collaboration through integrated platforms are highlighted. However, it faces challenges such as lack of quality data, limited infrastructure and challenges in integration with traditional methods. AI, combined with conservation practices, has great potential to transform environmental management, provided that obstacles related to access, training and ethical use are overcome.